Un texte prémontré inédit : Les Miracula beate Marie de Malaise par Jean de Rotselaar (1273) - Delmaire, Bernard (Analecta Praemonstratensia, 2001)
In the year 1273 John of Rotselaar, known as abbot of Averbode from 1289-1303, wrote an collection of Miracula beate Marie de Malaise, requested by the Premonstratensians from Château-l'Abbaye near Valenciennes. This work is unknown until today, because it was hidden in a chartulary of the abbey (Archives départementales du Nord in Lille). This article gives the first edition, together with an introduction, an anlysis and a list of names. The church Notre-Dame de Malaise in the village Bruille-saint-Amand was the centre of a little pilgrimage to the Blessed Virgin. The 24 conserved reports are relevant to the history of religion, the history of customs, the medicine and the ordinary life in the middle ages.
Keywords: 📚 premonstratensian (general)